Maternal immunization of mice with group B streptococcal type III polysaccharide-beta C protein conjugate elicits protective antibody to multiple serotypes. - Madoff, L C; Paoletti, L C; Tai, J Y; Kasper, D L (The Journal of Clinical Investigation, 1994)
Group B streptococcal infection is a major cause of neonatal mortality. Antibody to the capsular polysaccharide protects against invasive neonatal disease, but immunization with capsular polysaccharides fails to elicit protective antibody in many recipients. Conjugation of the polysaccharide to tetanus toxoid has been shown to increase immune response to the polysaccharide. In animal models, C proteins of group B streptococci are also protective determinants. We examined the ability of the beta C protein to serve in the dual role of carrier for the polysaccharide and protective immunogen. Type III polysaccharide was covalently coupled to beta C protein by reductive amination. Immunization of rabbits with the polysaccharide-protein conjugate elicited high titers of antibody to both components, and the serum induced opsonophagocytic killing of type III, Ia/C, and Ib/C strains of group B streptococci. Female mice were immunized with the conjugate vaccine and then bred; 93% of neonatal pups born to these dams vaccinated with conjugate survived type III group B streptococcal challenge and 76% survived type Ia/C challenge, compared with 3% and 8% survival, respectively, in controls (P < 0.001). The beta C protein acted as an effective carrier for the type III polysaccharide while simultaneously induced protective immunity against beta C protein--containing strains of group B streptococci. Images